Letter (copy) : Report of Medical Officer of Health for the Borough of Eastleigh - Tewson, Vincent
1938-07-16 038-0125-001 Secretary's. HVT/FC/DT/701. 16th July, 1938. Mr. J.A. McGuinness, Eastleigh Trades Council, 15, Spencer Road, EASTLEIGH. Dear Mr. McGuinness, REPORT OF MEDICAL OFFICER OF HEALTH FOR THE BOROUGH OF EASTLEIGH. Further to my letter of the 4th July I am returning the Report of the Medical Officer of Health for Eastleigh and also the copy of the Eastleigh Weekly News regarding tne Basque Childrens' Camp. I think that on the whole to attempt to remove any impressions that may have been given by the Report would only bring the matter into the public eye again and renew controversy. Many thanks for letting me have the documents. Yours sincerely, Assistant Secretary. Documents. 292/946/38/125(I)